2008
DOI: 10.1152/ajpcell.00139.2008
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of GTP dissociation inhibitor by PKA negatively regulates RhoA

Abstract: The cAMP-PKA cascade is a recognized signaling pathway important in inhibition of inflammatory injury events such as endothelial permeability and leucocyte trafficking, and a critical target of regulation is believed to be inhibition of Rho proteins. Here, we hypothesize that PKA directly phosphorylates GTP dissociation inhibitor (GDI) to negatively regulate Rho activity. Amino acid analysis of GDIalpha showed two potential protein kinase A (PKA) phosphorylation motifs, Ser(174) and Thr(182). Using in vitro ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
5
36
2
Order By: Relevance
“…In particular, Rho GTPases are involved in the development of pain memory by modulating dendritic spine morphology and density in the SCDH (20,21). Several studies have shown that the phosphorylation of GDI is capable of inducing the dissociation of GDI from Rho GTPase, resulting in the activation of Rho GTPase (22)(23)(24). In the present study, the phosphorylation level of GDI1 was not changed in the inflammatory pain model compared to the control, but EA treatment decreased the phosphorylation level.…”
Section: Discussioncontrasting
confidence: 47%
“…In particular, Rho GTPases are involved in the development of pain memory by modulating dendritic spine morphology and density in the SCDH (20,21). Several studies have shown that the phosphorylation of GDI is capable of inducing the dissociation of GDI from Rho GTPase, resulting in the activation of Rho GTPase (22)(23)(24). In the present study, the phosphorylation level of GDI1 was not changed in the inflammatory pain model compared to the control, but EA treatment decreased the phosphorylation level.…”
Section: Discussioncontrasting
confidence: 47%
“…RhoGDI␣ is phosphorylated by PAK1 at Ser101 and Ser174 and by PKA at Ser174 (26,27), and the phosphorylation events lead to dissociation and subsequent activation of Rac1 and RhoA. However, it is unclear how phosphorylation of RhoGDI␣ leads to the release of these GTPases.…”
Section: Discussionmentioning
confidence: 99%
“…RhoGDI␣-Ser174 has been shown to be phosphorylated by PAK1 and protein kinase A (PKA) (26,27), and this phosphorylation promotes its dissociation from either Rac1 or RhoA. Therefore, we speculated that 14-3-3 could associate with RhoGDI␣, and this binding led to the release of Rho GTPases from RhoGDI␣, promoting the activation of Rho GTPases upon ligand stimulation.…”
Section: -3-3 Promotes Cell Invasiveness and Reduces Adhesion Inmentioning
confidence: 99%
“…(32,33). Moreover, PKA activation in endothelial cells can result in inhibition of Rho kinase by direct phosphorylation of Rho GDPdissociation inhibitor (RhoGDI), thus preventing the release of the barrier-disruptive RhoA from the RhoA-RhoGDI complex (34). Besides, cAMP potentiates VE-cadherin-mediated cell-cell contacts, thus enhancing endothelial barrier function (32,33).…”
Section: Discussionmentioning
confidence: 99%